Challenges and Opportunities in Drug Administration: The Twelve Tasks of Infusorix! - Bussières Jean-François (Pharmaceutical Technology in Hospital Pharmacy, 2017)
The objective of this paper was to present 12 examples of the challenges of parenteral drug administration that hospital pharmacists and other clinicians face. These examples were presented as part of a talk during the International Symposium on Infusion Technologies in November 2016. Issues included the safety and compatibility of syringes, filtration, smart pumps, beyond-use dates, closed-system transfer devices, risk measurement, traceability and labeling.